New Avenues for Automated Railway Safety Information Processing in Enterprise Architecture: An NLP Approach - Abdul Wahab Qurashi; Zohaib A. Farhat; Violeta Holmes; Anju P. Johnson (IEEE Access, 2023)
Enterprise Architecture (EA) is crucial in any organisation as it defines the basic building blocks of a business. It is typically presented as a set of documents that help all departments understand the business model. In EA, safety documents are used to manage and understand safety risks. A novel similarity system for railway safety document processing is presented in this work. It measures the feasibility of automated updating of EA models with the Rule Book by verifying whether Rail Safety and Standards Board (RSSB’s) Rule Book clauses are present and complete in existing EA models. Additionally, a Natural Language Processing (NLP) based search feature was developed to drill through the database to find similar existing rules, principles, and clauses based on semantic similarity. The result will display the most similar clauses and rules with similarity scores and document names. In this study, different pre-trained Electra Small, DistilBERT (Distillation Bidirectional Encoder Representations from Transformers) Base and BERT (Bidirectional Encoder Representations from Transformers) Base were used to embed text. Additionally, the similarity between document rules was measured by cosine similarity metrics. With conclusive evidence, our findings show that BERT Base exceeds the other embedding methods in the semantic comparison of documents.